Factors that Influence Fan’s Attendance at Individual Sporting Events in Egypt through Coaches’ and Media Perspective - Aly, Ezzeldin R.; Hodge, Desmond S. (European Scientific Journal, ESJ, 2020)
Egypt has been long reflected as one of the most attractive countries to visit because of its historical treasure. Egypt also has remarkable athletic performances in the world championship and the Olympics. Egypt’s first recent Olympic gold medal was during the Athens Olympic Games. However, fans’ attendance at individual sporting events was not equivalent to fan presence at team sports. Related studies about fans’ who participate in different sporting events focused on men’s sports, team sports, and professional sports ( Armstrong, 2007). The sports development pyramid model by Casey (1988), designed to analyze the stages of sports development, was used to understand more about the association of the significance ofspecific factorsthat Influence fans’, and fan attendance at different individual sporting events in Egypt. A survey initially designed by the researchers was used to collect insights from seven (7) sports journalists, and twenty-seven (27) national team head coaches from different countries, who attended the African and the Arab games held in Cairo, Egypt. The results showed a significant relationship between fan attendance and individual sporting events, public relations, social media, cultural, and the actions of the Egyptian National Governing Bodies (ENGB). The result of this study further suggests the importance of implementing marketing strategies to promote individual sport.